2020
DOI: 10.1177/1948550620929452
|View full text |Cite
|
Sign up to set email alerts
|

System Justification and Perceptions of Group-Based Discrimination: Investigating the Temporal Order of the Ideologically Motivated Minimization (or Exaggeration) of Discrimination Across Low- and High-Status Groups

Abstract: Believing that social systems are fair confers palliative benefits via different mechanisms. Although the minimization of group-based discrimination plays a central role in this process, the direction of this association is contested. We address this debate by using eight waves of nationally representative longitudinal panel data to model the temporal ordering of system justification (SJ) and perceptions of group-based discrimination across ethnic minorities ( n = 7,159) and Whites ( n = 18,140). Cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 53 publications
2
20
0
3
Order By: Relevance
“…Similar patterns have been found among sexual minorities in the United States (Suppes et al, 2019) and Chile (Bahamondes et al, 2020). Moreover, a recent longitudinal study found that system-justifying beliefs decrease perceptions of discrimination among minorities (but not vice versa; see Bahamondes et al, 2021).…”
Section: What About Ethnic Minorities?mentioning
confidence: 99%
See 2 more Smart Citations
“…Similar patterns have been found among sexual minorities in the United States (Suppes et al, 2019) and Chile (Bahamondes et al, 2020). Moreover, a recent longitudinal study found that system-justifying beliefs decrease perceptions of discrimination among minorities (but not vice versa; see Bahamondes et al, 2021).…”
Section: What About Ethnic Minorities?mentioning
confidence: 99%
“…System-justifying beliefs also significantly increase perceptions of reverse discrimination among Whites (Major, Gramzow, et al, 2002; Wellman et al, 2016). More recently, Bahamondes et al (2021) showed that system justification increased perceptions of discrimination among ethnic majority group members. But perhaps more interestingly, perceptions of discrimination also increased system justification—a bidirectional association that may reflect a compensatory mechanism akin to in-group identification among the disadvantaged (see Sengupta et al, 2019).…”
Section: Perceptions Of Reverse Discrimination and The Desire For Gro...mentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, political attitudes appear to develop later in life (see Jennings & Niemi, 1981). More pertinent to the current study, some argue that perceived discrimination precedes system justification (as our results suggest; e.g., Suppes et al, 2019), while others argue that system justification fosters perceptions of discrimination (e.g., Bahamondes et al, 2020;McCoy & Major, 2007). Additional research is needed to examine the causal direction between perceived discrimination and system justification among women (vs. men) who have a chronic need for epistemic certainty.…”
Section: Discussionmentioning
confidence: 72%
“…Thus, epistemic needs may be particularly strong predictors of system justification among women. However, as justifying the system still conflicts with women’s group and self-interests, unlike for advantaged individuals, reducing perceptions of discrimination will not fully equalize control for women and thus they will still show lower system justification overall compared to men (Bahamondes et al, 2020; Jost et al, 2010).…”
Section: System Justification Theorymentioning
confidence: 99%